The problem of lending to agricultural enterprises in the context of the COVID-19 pandemic - Yekimov Sergey; Guzhina Galina; Lukyanov Pavel; Bespalova Olga; Kucherenko Dmitriy (E3S Web of Conferences, 2021)
The main obstacle to the implementation of lending to agricultural enterprises is the high cost of credit. In our opinion, an adequate state agricultural policy should increase the interest of commercial banks in providing loans. In our opinion, it should be aimed at increasing the availability of bank loans for agricultural enterprises. For this purpose, it is advisable to partially compensate the payment of bank interest by agricultural enterprises. In the world practice in the banking sector, negative rates of return on deposits have found application. Commercial banks are able to borrow money at a discount rate. At the moment, there is a practice according to which the Central Bank has only one discount rate. In our opinion, there could be several discount rates at the same time. We hold the view that depending on the purposes to which the commercial bank directs the funds received from the Central Bank, the size of the Central Bank’s discount rate may be different and even have a negative value. We believe that the negative discount rate applied by the central bank for lending to commercial banks to continue providing loans for the purchase of agricultural machinery could encourage them to issue loans to agricultural enterprises. In our opinion, the use of a negative discount rate of the Central Bank in some cases may contribute to the realization of the bank’s credit potential and enhance its lending activities.